ESTIMATION AND MINIMIZATION OF HARMONICS IN IEEE 13 BUS DISTRIBUTION SYSTEM WITH ADJUSTABLE SPEED DRIVE LOADS USING PASSIVE FILTERS - Nureni, Nureni; Sofyan, Sofyan; Akhmad, Satriani Said; Naim, Kurniawati; Fitiati, Andi; Sanjaya, Lari Andres (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
Improving power quality in electrical distribution systems is increasingly important with the increasing use of nonlinear loads, such as Adjustable Speed Drive (ASD), which can produce harmonies. This harmonic has the potential to damage equipment, reduce system efficiency, and interfere with power quality. Distribution systems such as IEEE 13 Bus are often used for power quality management analysis. Through simulation, researchers can identify the source and impact of harmonics and evaluate solutions, such as the application of passive filters that absorb or divert harmonic currents, to reduce their negative effects in the distribution system. In this study, two power sources, several transformers, static loads, and nonlinear loads in the form of Adjustable Speed Drive (ASD) were used. The simulation was carried out using Simulink R2019b to model the distribution network, generators, transformers, and loads. The simulation results show that the Adjustable Speed Drive (ASD) load can produce a total harmonic current distortion (THDi) of 24.62% in bus 7, while the total harmonic voltage distortion (THDv) is 0.97%. To minimize harmonic values, passive filters with variations of RL, RC, LC, and RLC are used. The results show that the use of RL passive filters is more effective in reducing THDi and THDv values in bus 7 by 24.47% and 0.97%.